"How Do You Want to be Wise?": The Influence of the Progymnasmata on Ælfrīc's Colloquy. Issue 1 (2nd January 2016) - Loveridge, Jordan
ABSTRACT: This essay analyzes the tenth-century pedagogical text Ælfrīc's Colloquy as an instance of Anglo-Saxon rhetorical instruction in the spirit of the Greco-Roman progymnasmata. Through a comparison of the text with classical sources such as Priscian's adaptations of Hermogenes and Isidore's Etymologies, this essay concludes that Ælfrīc knew of the progymnasmata and that these exercises served as the basis for rhetorical instruction that emphasized Benedictine ideals of communal concord through trained speaking and writing. Drawing on the commonplace of the three estates, the Colloquy demonstrated the ideal role of rhetoric in Anglo-Saxon society while modeling traditional progymnasmata exercises such as fable composition, impersonations, and comparisons.